(untitled) (Annals of Medical Research, 2021)
Aim: Serum lactate level is known to have prognostic value in critical patients. Tissue hypoxia is a cause of an increase in lactate levels. A decrease in excretion and metabolism of lactate can increase lactate levels. In this study, we have investigated whether clearance of serum lactate could be a predictor of mortality in critically ill intubated patients at the emergency room.Materials and Methods: Study Groups. Data of 205 critically ill patients requiring intubation, admitted to the emergency department of Haydarpasa Numune Training and Research Hospital between January 2011 and December 2015 have been scanned retrospectively. The intubations were performed according to the latest rapid sequence intubation protocols. Results: There were 100 (48.8%) male and 105 (51.2%) female patients. Median, minimum, and maximum age were 76,19, and 104, respectively. The number of patients who could not survive was 157 (76.6%). The median, maximum, and minimum age in the non-survivor group were 78,31, and 104, while they were 70,19, and 90 in the survivor group, respectively. The difference was statistically significant (p0.001). Final diagnoses and mortality rates of the critically ill patients requiring intubation in the emergency department are shown in Table 1. Conclusion: We have found out that lactate clearance has no statistically significant relationship with mortality (p=0.5). However, lactate levels were higher in the groups with mortality, and the difference was statistically significant for both referral time and 4th-hour blood samples (p=0.024 and 0.014, respectively).